Winterdark house - Turner, Jess, author; Dungy, Camille T., advisor; Beachy-Quick, Dan, committee member; Harrow, Del, committee member; Candelaria Fletcher, Harrison, committee member (Colorado State University. Libraries, 2021)
Winterdark House navigates the wounds and gaps left by grief—grief of the loss of a father to addiction, grief of the loss of the speaker to mental health struggles, grief of the loss of an aunt and a friend to drunk drivers. Moreover, this collection calls on memory in the hopes of answering questions of inheritance and loss. Winterdark House is very much concerned with the domestic, a house—the spaces we keep or attempt to keep. While investigating the artifacts inside of the house, the speaker, too, steps outside—turning to the natural world—where she might find more answers regarding family, mourning, and existence.
Keywords: family; house; poetry; grief; addiction; inheritance